CTL immunogenicity of Rv3615c antigen and diagnostic performances of an ESAT-6/CFP-10/Rv3615c antigen cocktail for Mycobacterium tuberculosis infection. (December 2017) - Tan, Shuguang; Lin, Nan; Huang, Mingxiang; Wang, Qing; Tan, Yunhong; Li, Bingxi; Zhang, Ning; Guo, Tianling; Cui, Yingbin; Chen, Xinchao; Wang, Dongping; Wang, Jue; et al.
Abstract: T cell immune responses have played pivotal roles in host immune protection against Mycobacterium tuberculosis (MTB) infection. MTB specific antigen, Rv3615c (EspC), was identified to be as immunodominant as the well-known ESAT-6 and CFP-10, and has brought promising expectations to more sensitive T-cell based diagnosis and vaccine development. However, limited knowledge about the immunogenicity and diagnostic values of this antigen has restricted its application in clinical practice. Herein, the Rv3615c antigen was identified as a robust CTL immunoantigen with broadly cross-human leucocyte antigen (HLA) allele recognized peptides which may contribute to the broad recognition of Rv3615c antigen among the population. A three-antigen-cocktail (3-Ag-cocktail) comprising of ESAT-6, CFP-10 and Rv3615c was investigated in a multicenter, randomized and double-blinded study to evaluate its clinical diagnostic performances. A significantly improved sensitivity was demonstrated against the 3-Ag-cocktail compared with that against ESAT-6 and CFP-10. Both responsive magnitude and sensitivity were significantly lower in patients concurrently suffering from cancer, indicating its restriction in diagnosis of immunocomprised patients. In conclusion, inclusion of the Rv3615c antigen with multiple HLA restricted CTL epitopes would benefit the T-cell based diagnosis of MTB infection.